Managing type 2 diabetes or prediabetes and binge eating disorder: a qualitative study of patients’ perceptions and lived experiences - Meg G. Salvia; Marilyn D. Ritholz; Katherine L.E. Craigen; Paula A. Quatromoni (Journal of Eating Disorders, 2022)
Abstract Background The overlap in prevalence between type 2 diabetes and binge eating disorder is substantial, with adverse physical and mental health consequences. Little is known about patients’ efforts at managing these two conditions simultaneously. The research objective was to explore patients’ experiences managing co-existing type 2 diabetes or prediabetes and binge eating disorder. Methods This is a qualitative descriptive study using semi-structured interviews. Participants included 21 women with type 2 diabetes or prediabetes (90% non-Hispanic White; mean age 49 ± 14.8 years, mean BMI 43.8 ± 8.4; 48% with type 2 diabetes and mean HbA1c was 8.4%). Interviews were analyzed using thematic analysis and NVivo software. Results Qualitative analysis revealed that participants reported binge episodes frequently started in childhood or adolescence and went undiagnosed for decades; notably, they recalled that diabetes diagnosis preceded the binge eating disorder diagnosis. They also described trying to lose weight throughout their lives and how feelings of deprivation, shame, and failure exacerbated binge eating. Participants further reported how binge eating made diabetes self-care and outcomes worse. Finally, participants observed that when binge eating disorder treatment and diabetes management were synergistically integrated, they experienced improvements in both binge eating and glycemic outcomes. This integration included reframing negative thoughts surrounding binge eating disorder and diabetes self-management and increasing their understanding of how the two disorders were inter-related. Conclusion Findings highlight the importance of increasing healthcare providers’ awareness of and screening for binge eating disorder in the treatment of diabetes and inform specific integrated interventions that address both diagnoses. Plain ENGLISH summary From this study where we interviewed 21 women with binge eating disorder (BED) and type 2 diabetes/prediabetes, we learned how binge eating impacted diabetes management and how diabetes impacted BED. Most participants reported receiving the diabetes diagnosis before being diagnosed with BED despite the earlier onset of binge eating, pointing to the need for BED screening. Participants described trying to lose weight throughout their lives and reported feelings of failure and shame, which made binge eating worse. Binge eating made diabetes management harder, but when diabetes and BED treatment were aligned, participants experienced improvements in binge symptoms and diabetes outcomes.